Digital-Based Education to Increase Knowledge in Healthy and Clean Environmental Management in Pagerwesi Trucuk Village, Bojonegoro - Ferawati, Ferawati; Efendi, Yusuf; Rizky K, Fitria; Nurmalita Sari, Rafika; Nur Isni Rohmatin (LPPM ISTeK ICsada Bojonegoro, 2026)
Healthy and clean environmental management is a crucial effort in improving public health, particularly among adolescents as agents of behavioral change. This Community Service Program aims to increase community knowledge, awareness, and digital literacy in healthy and clean environmental management through digital-based education. The program was conducted in Pagerwesi Village, Trucuk District, Bojonegoro Regency on June 24, 2025, primarily targeting adolescents and village health cadres. The implementation method included preparation, implementation, evaluation, and program sustainability, with an educational approach using digital media in the form of animated videos distributed through the WhatsApp platform. Evaluation was conducted through pre-tests and post-tests to measure the increase in participants' knowledge regarding Clean and Healthy Living Behavior (PHBS). The results of the activity showed an average increase in participant knowledge of 77.3%, categorized as good. Participants also demonstrated a positive attitude, high enthusiasm, and commitment to implementing PHBS in school and community environments. In addition, this program strengthened collaboration between universities, village governments, and external partners in community-based health development efforts. Digital-based education has proven effective as an innovation in community service to increase understanding and awareness of sustainable healthy and clean environmental management.